Development of Direct Compression Continuous Manufacturing System for Low-Dose Drug Products - Fushimi, Shinsuke; Horibe, Masashi; Sonoda, Ryoichi; Takusagawa, Shota; Watano, Satoru (Funtai Kogakkaishi, 2020)
A continuous direct compression process for a low-dose drug product was proposed. Acetaminophen was used for the model drug, and the mixing and tableting experiments with the low content were conducted using direct compression continuous manufacturing system. A low-dose continuous mixing was conducted in two steps. It was found that it is important to select the similar particle size for both drug and excipient in the first step mixing, and the result of the tableting experiment, the tablet contained 1% API indicated the good content uniformity. The experimental result of the second step, it was difficult to obtain the tablet contained 0.01% API with the good content uniformity. It was suggested that it is important to use jet-milled drug instead of using non-pulverized drug in the second step.